Calculating Recommended Fertilizer Rates for Vegetables Grown in Raised-Bed, Mulched Cultural Systems - George Hochmuth; Edward Hanlon (EDIS)
SL-303, a 6-page illustrated fact sheet by George Hochmuth and Edward Hanlon, explains the linear bed foot (LBF) concept and provides easy-to-use tables for converting a fertilizer recommendation from pounds per acre to pounds per 100 LBF. Published by the UF Department of Soil and Water Science, July 2009.